Factors Affecting Development of Medical Tourism Industry in West Azerbaijan Province of Iran - Mahmoudifar 1, Yousef; Tabibi 1*, Seyed Jamaledin; Nasiripour 1, Amir Ashkan; Riahi 1, Leila (Shahroud Journal of Medical Sciences, 2017)
Background: The market of medical tourism is considered as a revenue and competitive industry throughout the world, it is also regarded as a novel field of the advanced tourism. Therefore, most of the developing countries have focused on the medical tourism industry and they are planning for implementing it. In 2016, the present research was conducted with the main objective of designing a model for medical tourism development in West Azerbaijan province of Iran.Methods: This study is a cross-sectional study. The statistical population consisted of 40 interviewees who were selected via targeted sampling. The scholar-made questionnaire and studies of the Ricafort and Kazemi were employed as the tools of collecting data. The PLS software was utilized for analyzing data.Results: The results showed that two main factors, including hospital selection with an impact factor of 0.143 and West Azerbaijan province selection with impact factor of 0.466 had both direct and significant impact on development of medical tourism. The impact factor of all approaches on development of medical tourism was obtained positive and significant (P≤0.001).Conclusions: For development of medical tourism industry in West Azerbaijan province, attention to elements such as the appropriate conditions to attract medical tourism, according to political, legal, and regional economic development is effective.